(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SUMMARY: 1. Problem description - 2. Business based on commercial “surrogacy” is immoral and inhuman in nature, can be defined as the organisation and implementation of hidden child trafficking and mediation in such trade - 3. Illegal presumption and positioning of a child (whose birth “surrogacy” is aimed at) as an object of a commercial transaction, which is endowed with the characteristics of a product and consumer commodity properties, in “surrogacy” transactions - 4. Ideologically motivated, manipulative substitution of the concepts of the mother of the child and a woman-donor of an ovum, claiming to have a child born as a result of the “surrogacy” technologies use - 5. The practice of “surrogacy” is a gross violation of the child’s rights, first of all, the child’s right to his/her natural mother - 6. Legal and actual inconsistency and defectiveness of classifying commercially motivated “surrogacy” as an assisted reproductive technology and a form of high-tech or other medical care - 7. Reduction of the value and role of a woman as the mother to the value and role of a paid, commercially exploited living “human incubator”, a means of production by technology and the industry of “surrogacy” - 8. Risks of using children “obtained” as a result of “surrogacy” for criminal purposes - 9. Conclusions. ABSTRACT: This article presents a critical legal and bioethical analysis of the legal framework and practice of using the technology of commercial surrogacy («surrogate motherhood») - as a paid service provided in the interests of a third party (customers, third parties) with the subsequent transfer ("alienation") of this child to the customer of such a service. In conclusion a moral assessment of such actions is given.